The Specialist in Medicines Development (SMD) as a Vocational Program in Pharmaceutical Medicine: The Japanese and Italian Experience - Criscuolo, Domenico; Imamura, Kyoko; Klingmann, Ingrid (Frontiers in Pharmacology, 2020)
The growing complexity of the drug development process requires globally recognised professionals who have not only completed the cognitive path of competence, i.e. the specialized post graduate course in Pharmaceutical Medicine, but suggests that these individuals should join a vocational training program in order to consolidate the seven competencies which characterize a competent Pharmaceutical Professional. The Specialist in Medicines Development (SMD) program developed by the IMI project PharmaTrain and further supported by the IMI project IMI-TRAIN can be considered a prototype vocational program. In order to test the SMD value, it was implemented in two countries, Japan and Italy. The preliminary results, after three years of its implementation, are here summarized, and some initial recommendations are offered to all other countries which may consider to establish this program.